The Effect Of Career Development And Work Motivation On The Lamongan District DPRD Secretariat Employee Performance - Hayati, Erna; Rifatul Chasanah; Frisca Dinda Melania; Awaliyah Ramadhani Oktaviani; Maulida El Salbiyah; Meyalda Jasmine Shayna; Akhmad Sheva Pratama; Erik Fajar Setiawan; Dhea Muzdalifah (Jurnal Multidisiplin Sahombu, 2025)
This research aims to investigate the influence of career development and work motivation on the Regional People’s Representative Council (DPRD) Secretariat of Lamongan District employees’ performance. The sample used consisted of 35 respondents from the Lamongan District DPRD Secretariat. The software used in the data analysis of this research is SPSS with the multiple linear regression analysis method. The results in this study reveal that career development and work motivation affected the Lamongan District DPRD Secretariat employees’ performance. Additionally, both variables also have a significant influence with a contribution of 69,9%. The findings of this research could be helpful as a guidance for the leadership and policymarkers at the Lamongan District DPRD Secretariat with the aim of improving employee performance.